Cervical ectopic pregnancy. A case report - Ruipérez Pacheco, Estefanía (2019)
Cervical ectopic gestation is extremely rare, currently representing 0.1% of ectopic pregnancies. There is a high risk of bleeding due to the proximity between the uterine arteries and the cervix. In most cases, late diagnosis is associated with heavy bleeding and high mortality. We present a case of ectopic cervical pregnancy conservatively managed with intramuscular methotrexate, and we review the literature regarding diagnosis and treatment.